Effect of micro-galvanic corrosion on corrosion fatigue cracking of the weld joint of high strength bridge steel. (May 2023) - Li, Qi; Yao, Qiong; Sun, Liyang; Ma, Hongchi; Zhang, Chuang; Wang, Ning
Highlights: Corrosion fatigue failure mechanism of the high-strength steel weld joint was proposed. The Volta potential variation among various subzones induced the micro-galvanic corrosion. The micro-galvanic corrosion effect played a predominant role in the corrosion fatigue cracking of the weld joint. The micro-galvanic corrosion between WM and CGHAZ was confirmed by SKP and SECM. Abstract: The local electrochemical and corrosion fatigue cracking behavior of the weld joint of Q690qE high-strength bridge steel was investigated in simulated marine environment. It reveals the weld joint was vulnerable to corrosion fatigue failure in polluted marine atmosphere with the corrosion fatigue life considerably lower than that of parent metal. The micro-galvanic corrosion effect between CGHAZ and WM played a dominant role in the corrosion fatigue failure of the weld joint, leading to the final fracture mostly at CGHAZ. The micro-galvanic corrosion was caused by Volta potential variation among various subzones, which was evidenced by local electrochemical techniques.